Pendampingan Pengolahan Limbah Organik Berbasis Eco Enzyme di Kelurahan Cipancur Tahun 2021 - Kusmiyati; Rama Cipta Prasetya; Miftahul Hidayat (Pusat Riset dan Inovasi Nasional, 2021)
This research discusses community assistance activities in utilizing household waste, such as leftover vegetables, fruit and others, into organic fertilizer using eco enzyme technology. Eco enzyme is a solution resulting from the fermentation of organic materials with sugar and water which is useful for decomposing organic waste as well as becoming quality organic fertilizer. This assistance aims to empower communities to be able to utilize their own household waste into valuable input for agricultural and plantation activities. Apart from reducing environmental pollution due to careless waste disposal, the use of organic waste also opens up new economic opportunities for the community.